Model Integrasi Teknologi Digital dalam Pengembangan Karawitan PO Haryanto untuk Meningkatkan Minat Generasi Muda di Era Digital - Wijayanto, Wasis; Widyatma, Yollanda Vannesicha; Asmara, Fantasi Fana Sari; Fajri, Wahid Nur (GHURNITA: Jurnal Seni Karawitan, 2025)
This study discusses how karawitan laras PO Haryanto can play an active role in the scope of performing arts as a means of entertainment as well as an effective learning medium to increase the interest of the younger generation in traditional arts. The method used is qualitative through a case study approach. The data collection technique is carried out by means of observation, interviews, and documentation carried out at the PO Haryanto Kudus bus garage. This study explores the adaptation of karawitan learning activities in the art studio to digital media, namely streaming platforms, social media, and interactive content, as a form of cultural preservation and increasing the interest of the generation in developing the arts. The results of the study show that the collaboration between aspects of tradition and digital innovation is able to attract the attention of the next generation, and make karawitan relevant to entertainment tastes without eliminating the essence of local culture. This finding provides a new perspective on how karawitan art can maintain its existence in the digital era while also becoming a means of education for generations and conservation of traditional culture.